THE IMPORTANCE OF USING INDUSTRIAL WASTE AS A BINDER - Nasiba Vokhidova (European Science Publishing, 2025)
This study explores the use of industrial waste as a cost-effective, eco-friendly binder for briquetting low-grade iron- and carbon-bearing fines from blast-furnace and related metallurgical processes. Modified organo-mineral systems—combining mineral residues (e.g., slag, fly ash, and dust fines) with small amounts of organic additives—were prepared and evaluated. Laboratory briquettes were produced and tested for cold compressive strength, drop/shatter resistance, abrasion loss, water resistance, and thermal stability. The results show that organo-mineral binders derived from waste streams can generate briquettes with sufficient mechanical integrity for handling, storage, and pre-reduction, while reducing reliance on commercial binders. In addition, partial substitution of virgin materials with waste lowers binder cost and diverts significant volumes of by-products from landfill, supporting circular-economy goals. Process observations indicate that modest curing at ambient conditions is adequate, and that performance can be tuned by adjusting waste-to-additive ratios. Overall, using modified industrial waste as a binder offers a practical route to upgrade low-grade fines into a valuable feedstock for ironmaking and energy applications, with simultaneous economic and environmental benefits.
Keywords: Briquetting; organo-mineral binder; industrial waste; blast-furnace fines; circular economy; cold compressive strength.